The conceptual framing, design and evaluation of device ecologies for collaborative activities - Coughlan, Tim; Collins, Trevor D.; Adams, Anne; Rogers, Yvonne; Haya, Pablo A.; Martin, Estefania (Elsevier, 2012)
A variety of computing technologies, in addition to the personal computer, are now commonly used in many settings. As networking infrastructures mature, it is increasingly feasible and affordable to consider closer integration and use of these heterogeneous devices in tandem. However, little is known about how best to design or evaluate such ‘device ecologies’; in particular, how best to combine devices to achieve a desired type of collaborative user experience. A central concern is how users switch their attention between devices, to utilize the various elements to best effect. We describe here the development of an ecology of devices for groups of students to use when engaged in collaborative inquiry-learning activities. This included a multi-touch tabletop, laptops, projections, video streams and telephone. In situ studies of students and tutors using it in three different settings showed how individuals and groups switched their foci between the multiple devices. We present our findings, using a novel method for analysing users’ transitions between foci, identifying patterns and emergent characteristics. We then discuss the importance of designing for transitions that enable groups to appropriately utilise an ecology of devices, using the concepts of seams, bridges, niches and focal character.